Olive oil consumption and all-cause, cardiovascular and cancer mortality in an adult mediterranean population in Spain - Torres-Collado, Laura; García-de la Hera, Manuela; Lopes, Carla; Compañ-Gabucio, Laura María; Oncina-Cánovas, Alejandro; Notario-Barandiaran, Leyre; González-Palacios, Sandra; Vioque, Jesús (Frontiers in Nutrition, 2022)
Objective: We assessed the association between usual olive oil consumption (OOC) and all-cause, cardiovascular (CVD) and cancer mortality in an adult population in Spain. Methods: OOC was evaluated at baseline in 1,567 participants aged 20 years and older from the Valencia Nutrition Study in Spain using validated food frequency questionnaires. During an 18-year follow-up period, 317 died, 115 due to CVD and 82 due to cancer. Cox regression models were used to estimate adjusted hazard ratios (HR) and 95% confidence intervals (95%CI). Results: After adjusting for demographic and lifestyle factors, the OOC was associated with a lower risk of all-cause, CVD and cancer mortality. Compared to the less than once per month consumption, the consumption of up to one tablespoon per day was associated with a 9% lower risk of all-cause mortality (HR: 0.91; 95%CI: 0.68-1.22) and the consumption of 2 or more tablespoons with a 31% lower risk of all-cause mortality (HR: 0.69; 95%CI: 0.50-0.93; p-trend=0.011). The consumption of 2 or more tablespoons per day was also associated with lower risk of mortality for CVD (HR: 0.54; 95%CI: 0.32-0.91; p-trend =0.018) and cancer (HR: 0.49, 95%CI: 0.26-0.94; p-trend=0.019). Conclusion: Higher olive oil consumption was associated with lower long-term risk of all-cause, CVD and cancer mortality in an adult Mediterranean population. The maximum benefit was observed for the consumption of two or more tablespoons per day.